1998
DOI: 10.1029/97jc01918
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of nonlinear internal waves in the East and South China Seas

Abstract: Abstract. Synthetic Aperture Radar (SAR) images from ERS-1 have been used to study the characteristics of internal waves northeast and south of Taiwan in the East China Sea, and east of Hainan Island in the South China Sea. Rank-ordered packets of internal solitons propagating shoreward from the edge of the continental shelf were observed in the SAR images. On the basis of the assumption of a semidiurnal tidal origin, the wave speed can be estimated and is consistent with the internal wave theory. By using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
283
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 379 publications
(295 citation statements)
references
References 16 publications
6
283
0
1
Order By: Relevance
“…Then, with increasing and more detailed internal wave observations, it was found that several further factors should be included in the model. First of all, the variable depth along the wave path leads to wave amplitude variation, and even to the possible changing of the soliton polarity; this effect has also been recently studied in the South China Sea [Liu et al, 1998;Cai et al, 2002;Zhao et al, 2003]. Second, the horizontal variability of the density and background current field is important, particularly for the NWS situated at ~20S [Holloway et al, 1997].…”
Section: Generalized Korteweg-de Vries Equationmentioning
confidence: 99%
“…Then, with increasing and more detailed internal wave observations, it was found that several further factors should be included in the model. First of all, the variable depth along the wave path leads to wave amplitude variation, and even to the possible changing of the soliton polarity; this effect has also been recently studied in the South China Sea [Liu et al, 1998;Cai et al, 2002;Zhao et al, 2003]. Second, the horizontal variability of the density and background current field is important, particularly for the NWS situated at ~20S [Holloway et al, 1997].…”
Section: Generalized Korteweg-de Vries Equationmentioning
confidence: 99%
“…In our case, there are two elevation waves created behind the original depression wave (Figure 1). The ISW evolution in this phase has been studied by numerical method several times [Knickerbocker and Newell, 1980;Liu et al, 1998;Vlasenko and Hutter, 2002].…”
Section: Conversion Processmentioning
confidence: 99%
“…[11] The polarity of the ISWs described by the EKdV equation depends on the sign of the quadratic nonlinear coefficient a (except for the turning point where a is equal to zero) [Benjamin, 1966;Liu et al 1998]. Under conditions of a 60 m upper layer depth, the ISWs are depression waves when the water depth is deeper than 120 m (a < 0).…”
Section: Dynamics Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Once again, a single particle with a non-zero weight is used to represent each peakon. In the next set of numerical experiments, presented in Figures 6-9, we illustrate the emergent and collision properties of peakon wave fronts in 2-D -the phenomena that are observed in nature, for instance, as trains of internal waves in the south China Sea, [31]. The initial data for the examples below (shown in Figs.…”
Section: Numerical Examplesmentioning
confidence: 99%